Role of bombesin and cholecystokinin receptors in gastric injury induced by hemorrhagic shock in the rat - DENİZBAŞI ALTINOK, ARZU (KARGER, 2003)
Bombesin has been shown to have trophic effects on the gastrointestinal tissue. Bombesin has direct mitogenic effects besides stimulating release of gastric hormones. The aim of this study was to investigate the effect of bombesin in hemorrhagic shock-induced stress ulcers in rats, and the role of cholecystokinin (CCK) receptors in this activity. Hemorrhagic shock was created by withdrawing 3 ml blood/200 g b.w. of rats. At the end of the 1-hour hypovolemic shock period, histological analysis, gastric ulcer index, gastric myeloperoxidase activity and gastric protein oxidation levels were determined. When given before the hemorrhage, subcutaneous bombesin (10 mug/kg) reduced macroscopically gastric ulcer index (p < 0,05). Blockade of CCK-A receptors with intraperitoneal MK-329 (1 mg/kg) did not reverse bombesin-induced gastroprotection. Blockade of CCK-B receptors with intraperitoneal L-365,260 (25 mg/kg) reversed bombesin-induced gastroprotection. Blockade of the two receptors resulted in no gastroprotection at all. It is concluded that bombesin treatment attenuated hemorrhagic shock-induced stress ulcers in rats via CCK receptors. Copyright (C) 2003 S. Karger AG, Basel.
Keywords: bombesin; cholecystokinin receptors; gastric injury; stress ulcer; NITRIC-OXIDE; SECRETION; STIMULATION; INTESTINE; PEPTIDES; GROWTH